Developing the agile enterprise. (1st January 2002) - Bessant, John; Knowles, David; Briffa, Greg; Francis, David
The problem facing enterprises in the late 20th century can be seen as the latest version of two long-standing puzzles to do with responding to demanding internal and external environments. The continuing search for solutions to these puzzles leads to investment in innovation - via R&D, technology transfer, etc. But evidence suggests that the key requirement is not solving the puzzle for one set of circumstances but in continually solving the problems as the puzzles mutate. This places emphasis on organisational capability - it is not what you know or what you can buy but how well you learn and adapt which is the key. We term this "agility", and this paper explores the definition in terms of the "dynamic capability" view of strategic management. This paper draws on case study research being carried out as part of a major UK program of work looking at the development of agility in small and medium-sized manufacturing enterprises. The paper presents a reference model which seeks to explain and guide the development of agility within organisations.